A comparison of recent trends in precipitation and temperature over Western and Eastern Eurasia. (13th February 2018) - Zhao, Weihong; Du, Haibo; Wang, Lei; He, Hong S.; Wu, Zhengfang; Liu, Kai; Guo, Xiangyu; Yang, Yue
Abstract : Eurasia is one of the most sensitive areas to climate change in the world. Its western and eastern coasts are very likely to exhibit different temperature and precipitation variations in response to the global climate change. By using precipitation (PRCP), maximum temperature ( T max ), minimum temperature ( T min ), and daily temperature range (DTR) data from 333 meteorological stations in Western (WE) and Eastern Eurasia (EE), we quantitatively compared spatio‐temporal changes on both the seasonal and annual scales from 1961 to 2012. Results showed that PRCP mainly exhibited increasing trends in northern WE and decreasing trends in southern WE, whereas PRCP in EE recorded an increase–decrease–increase trend from high to low latitudes. The increase of annual PRCP in WE was higher than that in EE. On the seasonal scale, the PRCP in WE recorded an opposite trend from EE. T max and T min significantly increased for almost all stations on the annual and seasonal scales, especially during the winter. Nevertheless, the increase of T min was higher than that of T max in EE, resulting in a decreased DTR on both the seasonal and annual scales. An reverse trend of DTR was detected in WE. Our results concluded that the Arctic Oscillation was the major large‐scale atmospheric circulation affecting the trends of PRCP (negative correlation) and temperature (positive correlation) over WE and EE, and it might play an important role in future climate change. Abstract : Locations of the 219 meteorological stations in Western Eurasia (WE) and 114 weather stations in Eastern Eurasia (EE) that were utilized in this study, for which precipitation and temperature data collected during the period from 1961 to 2012 were analysed.